Analysis of Technical and Operational Aspects of the Buffet Seblak Angkringan Business in Gedangan Regency - Bilal Kautsar Setiabudi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
The Seblak Prasmanan angkringan business in Gedangan Regency has become a popular culinary destination, offering a variety of seblak menus with a buffet concept. This study aims to analyze the technical and operational aspects of this business to identify the factors that influence its success and operational efficiency. A qualitative and quantitative approach was used in this research, with data collection methods including direct observation, interviews with owners and employees, and analysis of operational documents.The results of the study show that technical aspects such as location selection, angkringan layout, and cooking equipment significantly affect operational smoothness. Additionally, operational management, including work schedule arrangements, raw material management, and customer service, plays an important role in maintaining quality and customer satisfaction. The main challenges faced are fluctuations in raw material availability and food waste management. This study concludes that the implementation of efficient operational strategies and innovation in service can enhance the competitiveness of the Seblak Prasmanan angkringan business in Gedangan Regency.